2022
DOI: 10.3389/fphar.2022.1034667
|View full text |Cite
|
Sign up to set email alerts
|

The emerging roles and therapeutic potential of B cells in sepsis

Abstract: Sepsis is a life-threatening syndrome caused by anomalous host response to infection. The pathogenesis of sepsis is complex, and immune dysfunction is the central link in its occurrence and development. The sepsis immune response is not a local and transient process but a complex and continuous process involving all major cell types of innate and adaptive immunity. B cells are traditionally studied for their ability to produce antibodies in the context of mediating humoral immunity. However, over the past few … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 145 publications
0
10
1
Order By: Relevance
“…Several studies have suggested that regulatory B-cell numbers are significantly increased in patients with sepsis; this aggravates immunosuppression owing to the secretion of IL-10 and IL-35. [22] …”
Section: Immune Response In Sepsismentioning
confidence: 99%
“…Several studies have suggested that regulatory B-cell numbers are significantly increased in patients with sepsis; this aggravates immunosuppression owing to the secretion of IL-10 and IL-35. [22] …”
Section: Immune Response In Sepsismentioning
confidence: 99%
“…Naïve B cells can be divided into two groups: B1 and B2 cells ( Figure 1 ). The former consists of B-1a and B-1b subsets, and the latter consists of marginal zone (MZ) and follicular (FO) B cells [ 29 ]. Mature B cells migrate to peripheral lymphoid tissue and can become active when encountering homologous antigens in a sepsis setting.…”
Section: The Development and Activation Of B Cellsmentioning
confidence: 99%
“…B lymphocytes are multifunctional immune cells that play an important role in both the adaptive and innate immune response, which is of great importance for preventing sepsis (8)(9)(10). However, sepsis results in a massive depletion of B cells, which exacerbates immunosuppression and is closely associated with poor prognosis (11)(12)(13)(14). Studies have indicated that B cell depletion is associated with apoptosis and different B cell subsets may be different in their sensitivity to apoptosis.…”
Section: Introductionmentioning
confidence: 99%